Hadis Pendidikan: Tela’ah Pemikiran Abu Laits As-Samarqandi tentang Hak-hak Anak dalam Kitab Tanbih Al-Ghafilin - Saeful Bahri (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
Abu Laits As-Samarqandi's thought offers intellectual wealth that is very relevant to be studied in the context of contemporary Islamic education. In the midst of various challenges and dynamics of Islamic education today, revisiting the ideas of classical figures such as As-Samarqandi becomes a necessity, not just a historical search. This research will answer two important questions of Abu Laits As-Samarqandi's thinking in the field of education about children's rights to parents and the status of the hadiths that are the basis of his thought which have been documented in the work of Tanbih Al-Ghafilin. According to the focus of the problem studied, this research uses a qualitative approach, the type of research is in the form of literature, and the analysis technique is taken with a comparative descriptive method. The results of his research show that, First, Abu Laits As-Samarqandi's thoughts on the rights of children that must be fulfilled by parents are: (1) post-birth obligations which include giving names, education, and marriage, (2) developing into filial children, (3) obtaining family happiness, and (4) forming good personalities, vertically and socially. Second, in terms of the status of the hadiths that are the main basis of his thought, Abu Laits does not mention his hadith sanad in detail, considering that the book Tanbih Al-Ghafilin is not a hadith book. After going through the study, it was found that some of them were sahih and dha'if, however, arguing with the hadith of dha'if is permissible in the context of education because it is the virtue of charity (fadha'il al-a'mal).